Wild Kratts. Around the world adventures [videorecording (DVD)]. - Kratt, Chris; Kratt, Martin (PBS Kids, 2020)
To the creature rescue! Join Chris Kratt and Martin Kratt as they embark on more than twenty action-packed adventures! Together, the brothers spring into action to rescue an injured endangered Florida panther and recover Aviva's precious family heirloom from the leaping Caracal cat. The fun continues as the Wild Kratts team hosts a Creature Power race to help them uncover the greatest running creatures, and as they come up with a plan after the Tortuga crashes somewhere in the middle of the Amazon rainforest!